Current Understanding of Guanylin Peptides Actions. (17th April 2013) - Sindic, Aleksandra
Abstract : Guanylin peptides (GPs) family includes guanylin (GN), uroguanylin (UGN), lymphoguanylin, and recently discovered renoguanylin. This growing family is proposed to be intestinal natriuretic peptides. After ingestion of a salty meal, GN and UGN are secreted into the intestinal lumen, where they inhibit sodium absorption and induce anion and water secretion. At the same conditions, those hormones stimulate renal electrolyte excretion by inducing natriuresis, kaliuresis, and diuresis and therefore prevent hypernatremia and hypervolemia after salty meals. In the intestine, a well-known receptor for GPs is guanylate cyclase C (GC-C) whose activation increases intracellular concentration of cGMP. However, in the kidney of GC-C-deficient mice, effects of GPs are unaltered, which could be by new cGMP-independent signaling pathway (G-protein-coupled receptor). This is not unusual as atrial natriuretic peptide also activates two different types of receptors: guanylate cylcase A and clearance receptor which is also G-protein coupled receptor. Physiological role of GPs in other organs (liver, pancreas, lung, sweat glands, and male reproductive system) needs to be discovered. However, it is known that they are involved in pathological conditions like cystic fibrosis, asthma, intestinal tumors, kidney and heart failure, obesity, and metabolic syndrome.